A new mouse model for female genital schistosomiasis. - Monica L Richardson; Chi-Ling Fu; Luke F Pennington; Jared D Honeycutt; Justin I Odegaard; Yi-Ju Hsieh; Olfat Hammam; Simon L Conti; Michael H Hsieh (Public Library of Science (PLoS), 2014)
Over 112 million people worldwide are infected with Schistosoma haematobium, one of the most prevalent schistosome species affecting humans. Female genital schistosomiasis (FGS) occurs when S. haematobium eggs are deposited into the female reproductive tract by adult worms, which can lead to pelvic pain, vaginal bleeding, genital disfigurement and infertility. Recent evidence suggests co-infection with S. haematobium increases the risks of contracting sexually transmitted diseases such as HIV. The associated mechanisms remain unclear due to the lack of a tractable animal model. We sought to create a mouse model conducive to the study of immune modulation and genitourinary changes that occur with FGS.To model FGS in mice, we injected S. haematobium eggs into the posterior vaginal walls of 30 female BALB/c mice. A control group of 20 female BALB/c mice were injected with uninfected LVG hamster tissue extract. Histology, flow cytometry and serum cytokine levels were assessed at 2, 4, 6, and 8 weeks post egg injection. Voiding studies were performed at 1 week post egg injection.Vaginal wall injection with S. haematobium eggs resulted in synchronous vaginal granuloma development within 2 weeks post-egg injection that persisted for at least 6 additional weeks. Flow cytometric analysis of vaginal granulomata revealed infiltration by CD4+ T cells with variable expression of the HIV co-receptors CXCR4 and CCR5. Granulomata also contained CD11b+F4/80+ cells (macrophages and eosinophils) as well as CXCR4+MerTK+ macrophages. Strikingly, vaginal wall-injected mice featured significant urinary frequency despite the posterior vagina being anatomically distant from the bladder. This may represent a previously unrecognized overactive bladder response to deposition of schistosome eggs in the vagina.We have established a new mouse model that could potentially enable novel studies of genital schistosomiasis in females. Ongoing studies will further explore the mechanisms by which HIV target cells may be drawn into FGS-associated vaginal granulomata.